Composition of high-molecular-weight glutenin subunits and gluten quality in wheat lines with alien genetic material - O. A. Orlovskaya; S. I. Vakula; L. V. Khotyleva; A. V. Kilchevsky (Труды по прикладной ботанике, генетике и селекции)
Background. High-molecular-weight glutenin subunits (HMW-GSs) make the greatest contribution to the formation of baking properties in bread wheat (Triticum aestivum L.). Glutenin polymorphism of bread wheat relatives is significantly richer than in cultivated varieties. The objective of this work was to identify the HMW-GS composition and assess the gluten quality of bread wheat lines with introgressions of alien genetic material.Materials and methods. We studied the parental varieties of spring bread wheat, accessions of the tetraploid and hexaploid Triticum L. species, and 19 introgressive lines produced with their participation. Glutenins were separated using sodium dodecyl sulfate polyacrylamide gel electrophoresis and HMW-GSs were identified using the Payne nomenclature system. Gluten quality was determined in accordance with GOST 13586.1-68 (the 2017–2019 and 2021–2022 growing seasons). Data processing was performed using the Statistica 10.0 and MS Excel software packages.Results and conclusion. HMW-GSs uncharacteristic of T. aestivum cultivars were identified in the studied accessions of T. dicoccoides (Körn. ex Aschers. et Graebn.) Schweinf., T. spelta L., and T. kiharae Dorof. et Migusch. These HMW-GSs are of interest for enriching the wheat gene pool. HMW-GSs of related species were found in 10 out of 19 introgressive lines. A five-year observation period revealed that wheat relatives on average significantly exceeded common wheat cultivars in gluten quality, and introgressive lines did not differ significantly from the parental genotypes. Lines with high rheological properties of gluten had, as a rule, HMW-GSs of related species in their composition.